2014
DOI: 10.1111/jog.12598
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ovarian cancer chemotherapy by delivery of multidrug‐resistance gene small interfering RNA using tumor targeting Salmonella

Abstract: Attenuated Salmonella typhi may represent a promising vector for in vivo administration of RNA interference therapy against malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Genetically attenuated bacteria such as attenuated Salmonella offers promise as an anticancer vector and has been widely used as a tool to deliver plasmids that express siRNA in vivo 1621 . Our previous studies have demonstrated that a combination of low-dose DDP with gene therapy expressing tumor protein p53 (p53) and mouse double minute 2 homolog (MDM2) siRNA, delivered by attenuated Salmonella enterica serovar Typhi vaccine strain Ty21a ( Salmonella Typhi Ty21a ), synergistically inhibited ovarian cancer and PCa growth without damaging normal tissues 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetically attenuated bacteria such as attenuated Salmonella offers promise as an anticancer vector and has been widely used as a tool to deliver plasmids that express siRNA in vivo 1621 . Our previous studies have demonstrated that a combination of low-dose DDP with gene therapy expressing tumor protein p53 (p53) and mouse double minute 2 homolog (MDM2) siRNA, delivered by attenuated Salmonella enterica serovar Typhi vaccine strain Ty21a ( Salmonella Typhi Ty21a ), synergistically inhibited ovarian cancer and PCa growth without damaging normal tissues 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…P-gp is a highly conserved membrane glycoprotein encoded by the MDR1 gene. In one study, Deng et al, assessed the effects of attenuated Salmonella typhi acting as a tumor-targeted vector to deliver small interfering RNA (siRNA) against the multidrug-resistance gene (MDR1) ( 45 ). This was tested in the cisplatin-resistant ovarian cancer cell line SKOV-3/DDP, to increase cisplatin sensitivity.…”
Section: Salmonella Bacteria As Delivery Systems For Anti-tumentioning
confidence: 99%
“…The tumor growth in mice was slower when treated with DDP. Attenuated Salmonella bacteria could be used for delivery of RNA interference as a component of cancer treatment ( 45 ).…”
Section: Salmonella Bacteria As Delivery Systems For Anti-tumentioning
confidence: 99%
“…The application of siRNAs in the attempt to interfere with tumors has been primarily at the cell culture level rather than the whole organism [108] . Nevertheless, this approach does open up a new way to modify tumor cells and a broad variety of delivery systems have been employed in studies on OC [126][127][128][129][130][131][132][133] . Table 2 gives an overview on the deregulated circulating miRNAs detected in plasma, serum, ascites, urine and exosomes from OC patients and their function in EMT, migration, invasion and metastasis.…”
Section: Sirnas and Mrnasmentioning
confidence: 99%